Alpha2-Antiplasmin: The Devil You Don't Know in Cerebrovascular and Cardiovascular Disease - Singh, Satish; Saleem, Sofiyan; Reed, Guy L. (Frontiers in Cardiovascular Medicine, 2020)
Alpha2-antiplasmin (α2AP), the fast, serine protease inhibitor (serpin) of plasmin, was originally thought to play a key role in protection against uncontrolled, plasmin-mediated proteolysis of coagulation factors and other molecules. However, studies of humans and mice with genetic deficiency of α2AP have expanded our understanding of this serpin, particularly in disease states. Epidemiology studies have shown an association between high α2AP levels and increased risk or poor outcome in cardiovascular diseases. Mechanistic studies in disease models indicate that α2AP stops the body’s own fibrinolytic system from dissolving pathologic thrombi that cause venous thrombosis, pulmonary embolism, arterial thrombosis and ischemic stroke. In addition, α2AP fosters the development of microvascular thrombosis and enhances matrix metalloproteinase-9 expression. Through these mechanisms and others, α2AP contributes to brain injury, hemorrhage and swelling in experimental ischemic stroke. Recent studies also show that α2AP is required for the development of stasis thrombosis by inhibiting the early activation of effective fibrinolysis. In this review, we will discuss the key role played by α2AP in controlling thrombosis and fibrinolysis and, we will consider its potential value as a therapeutic target in cardiovascular diseases and ischemic stroke.